Violência, afetos e luta por reconhecimento na criminalidade pauperizada - Pires, Artur (2023)
The article analyzes, from a comprehensive perspective, how the affectivities of impoverished criminal agents – apprehending psycho-emotional aspects within this approach – are related to their ways of operating illegal activities and their struggle for recognition. The main objective of this work is to discuss how the structural oppression of the dominant semiology causes, in different ways, unbalanced affectivities in the psyche of people involved in criminal relationships. The research that gave rise to this work has been developed since 2013 in the outskirts of Fortaleza, systematically since 2016, mainly in a complex of slums with approximately 30,000 inhabitants in the southeast region of the capital of Ceará. To collect empirical data, the methods used were spontaneous conversations in the research field, semi-structured interviews, direct observation and field diary. To obtain theoretical data, the methods were reading, filing and systematization of concepts. It is concluded that, in the face of structural oppression, impoverished criminal agents face a continuous and recurrent process of emotional exhaustion, mainly due to the risks of their activities. And it is from their violent practices that they undertake a struggle for recognition to compensate for a marginalized and oppressed subjectivity.